2011
DOI: 10.2527/jas.2010-3005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exposure of diets with reduced concentrations of aflatoxin and deoxynivalenol on growth and immune status of pigs1

Abstract: This study investigated the growth and immune responses of pigs fed diets containing reduced concentrations of aflatoxin (AF) and deoxynivalenol (DON) from naturally contaminated corn. Sixty gilts (13.9 ± 0.2 kg of BW) were randomly assigned to 4 treatments (5 replicate pens per treatment and 3 pigs per pen): A (a control diet without detectable AF and DON); B (a diet with 60 μg of AF/kg and 300 μg of DON/kg); C (a diet with 120 μg of AF/kg and 600 μg of DON/kg); and D (a diet with 180 μg of AF/kg and 900 μg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 36 publications
9
110
5
1
Order By: Relevance
“…Reduction of feed intake and consequent decrease of BW gain have been commonly observed when pigs are fed DON contaminated diets (Goyarts et al, 2005b;Chaytor et al, 2011b;Mok et al, 2013), and these were also observed in the present study. In addition, the ADFI of pigs fed the NC diet from d 0 to 7 was 24.3% less compared with those fed the PC diet, which was close to the predictive value (28.7%) of feed intake reduction calculated by the equation derived from the literature (Mok et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Reduction of feed intake and consequent decrease of BW gain have been commonly observed when pigs are fed DON contaminated diets (Goyarts et al, 2005b;Chaytor et al, 2011b;Mok et al, 2013), and these were also observed in the present study. In addition, the ADFI of pigs fed the NC diet from d 0 to 7 was 24.3% less compared with those fed the PC diet, which was close to the predictive value (28.7%) of feed intake reduction calculated by the equation derived from the literature (Mok et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have showed the up-regulation of serum immunoglobulin subsets in pigs fed diets containing Fusarium mycotoxins (Swamy et al, 2002;Goyarts et al, 2005b) whereas other studies showed no alteration of immunoglobulin subsets Chaytor et al, 2011b). In the present study, immunoglobulin subsets were not altered by feeding pigs with contaminated diets.…”
Section: Excretion Of Cell Wall Degrading Enzymes Bycontrasting
confidence: 62%
“…Pigs are known to be very sensitive to dietary DON (Pestka, 2007) which may cause reduced feed intake, weight loss and immune system disorders (CAST, 2003;Pinton et al, 2008;Chaytor et al, 2011b). The DON has also been reported to damage the intestinal tract by altering barrier function of epithelial cells (Pinton et al, 2010), which may adversely affect the digestion and absorption of nutrients in diets.…”
Section: Introductionmentioning
confidence: 97%
“…Besides their known carcinogenicity, AF cause immunosuppression in domestic animals and humans by impairing the innate and cell-mediated immunity (Chaytor et al, 2011;Gong et al, 2004;Luongo et al, 2013). Both cytolysis by natural killer (NK) cells and several macrophage functions, including phagocytosis, production of reactive oxygen species (ROS), and intracellular killing, are impaired by AF (Qureshi et al, 1998;Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%